Quantitative detection of T315I mutations of BCR::ABL1 using digital droplet polymerase chain reaction - Mu, Huijun; Zou, Jian; Zhang, Haiping (Hematology, Transfusion and Cell Therapy, 2024)
T315I mutations of the BCR::ABL1 gene lead to resistance to tyrosine kinase inhibitors (TKIs). This study evaluated the performance of digital droplet polymerase chain reaction (ddPCR) in quantifying T315I mutations and their frequency in Philadelphia chromosome (Ph) positive hematological patients. The course of disease and BCR::ABL1 fusion transcripts (e13a2, e14a2 and e1a2) were retrospectively reviewed in 21 patients with acute lymphoblastic leukemia (ALL) and 85 patients with chronic myeloid leukemia (CML). T315I mutation analysis was carried out using ddPCR and the limit of detection was assessed using mutant T315I DNA at varying variant allele fractions. T315I mutations were found in two ALL patients and one CML patient without remission in molecular biology and with mutation burdens of 29.20%, 40.85%, and 3.00%, respectively. The mutation burden of ALL patients was higher than that of CML patients, but there was no significant difference between the two (p-value = 0.0536). The test's limit of detection was 0.02% with a correlation coefficient greater than 0.99 between the expected and actual detection abundances. T315I mutations have a high incidence in Ph-positive ALL patients even if the course of disease is short. In molecular biology, T315I mutation detection is indicated for CML patients not in remission.